Computerized engine controls - Hatch, Steve V. (Delmar, Cengage Learning, 2012)
Delivering solid coverage of both domestic and imports, COMPUTERIZED ENGINE CONTROLS, 9e equips readers with the foundational knowledge needed to successfully diagnose and repair vehicle electronic systems. Reflecting the latest technological advances from the field, the Ninth Edition offers updated and expanded coverage of the approach of diagnostics, air/fuel ratio sensors, OBD II, and much more. This text includes in-depth insight into such cutting-edge topics as hybrid and fuel cell vehicles, GM's 42-volt system, hexadecimal conversion, multiplexing, and logic gates. Key concepts are reinforced with ASE-style, end-of-chapter questions to familiarize readers with the types of questions they are likely to see in certification testing.
Includes index.
Keywords: Automobiles -- Motors -- Computer control systems.; Automobiles -- Electronic equipment.; elektronické knihy; electronic books